Comparative Analysis of Immune Activation Markers of CD8+ T Cells in Lymph Nodes of Different Origins in SIV-Infected Chinese Rhesus Macaques - Liu, Jinbiao; Xiao, Qianhao; Zhou, Runhong; Wang, Yong; Xian, Qiaoyang; Ma, Tongcui; Zhuang, Ke; Zhou, Li; Guo, Deyin; Wang, Xu; Ho, Wen-Zhe; Li, Jieliang (Frontiers in Immunology, 2016)
Altered T-cell homeostasis, such as expansion of CD8+ T cells to the secondary lymphatic compartments has been suggested as a mechanism of HIV/SIV-pathogenesis. However, the role of immune activation of CD8+ T cells in the CD4/CD8 turnover and viral replication in these tissues is not completely understood. In the present study, we compared the expression of immune activation markers (CD69 and HLA-DR) on CD8+ T cells in the peripheral blood and lymph nodes (LNs) of SIV-infected/uninfected Chinese rhesus macaques. SIV-infected macaques had significantly higher percentages of CD8+CD69+ and CD8+HLA-DR+ T cells in all these anatomical compartments than uninfected macaques except for CD8+HLA-DR+ T cells in peripheral blood. LNs that located close to the gastrointestinal (GI) tract (colon, mesenteric and iliac LNs) of SIV-infected macaques had profoundly lower numbers of CD4+ T cells, but no significantly difference in expression of activation marker (CD8+CD69+ and CD8+HLA-DR+) as compared with the peripheral lymphatic tissues (axillary and inguinal LNs). The CD4/CD8 ratios were negatively correlated with the activation of CD8 T cells in the overall LNs, with further associations with CD8+HLA-DR+ in GI LNs while CD8+CD69+ in peripheral LNs. These observations demonstrate that the increase of CD8+ T cell activation is a contributing factor for the decline of CD4/CD8 ratios in GI system.